Perception on Use of Sanitary Napkins Among Students in Khammam Locality: a Survey - Arugula, Pooja; Paramasivam, Suresh Kumar; Kanuri, Niharika; Srirangam, Akhila; Vemuluri, Mounika (Indian Journal of Pharmacy Practice)
Background: We conducted a survey to analyze the student’s perception on sanitary napkins in Khammam locality. Method: To carry out our studies we started our work on November 2016 and completed by April 2017 during which we provided each student (around 500 students of age group 11-20 and 21-30) with a printed copy comprising of various queries regarding sanitary napkins. Based on the obtained data we found that, in students of both the age groups majority of the students are rarely experiencing discomfort, rashes (47.55% on average), majority of the students are not satisfied with the price (59.25% on average), most of the students are not at all having any idea about the chemicals used in sanitary napkins (57.29% on average), majority of students change their sanitary napkins at a time interval of 4-8 h (46.7% on average) and majority of students consider various factors like comfort, quality, price, size, package (37.75% on average) while choosing a sanitary napkin. Conclusion: Finally, we found out that most of the students are not satisfied with the price of the sanitary napkins and even they are not aware of the chemicals that are being used in the manufacturing of the sanitary napkins.
Keywords: Sanitary napkins; Survey; Perception; Students; Queries